Gum chewing stimulates early return of peristalsis after caesarean section - Siddhpura, Shivani T.; Ninama, Pallavi G.; Mehta, Latika R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The aim was to evaluate the efficacy and safety of postoperative gum chewing on the recovery of peristalsis after caesarean section. Study design was a randomized controlled study. Settings were at GMERS medical college and hospital, Sola, Ahmedabad. Population was total of 200 pregnant women who underwent caesarean section under spinal anaesthesia. Methods: Women were randomized into two groups. Group A who received 1 chewing gum for 15 minutes every 2 hours post-surgery. Group B had traditional management (oral intake of clear fluids after 12 hours). Results: The study group showed shorter mean interval time for return of bowel sounds, passage of flatus, passage of bowel motion and shorter hospital stay as compared to the control group. Conclusions: Chewing gum is safe post-CS, well tolerated and associated with rapid return of intestinal motility and shorter hospital stay.